Nano-porous composite electro-catalytic material as well as preparation method and application thereof
By using nanoporous composite electrocatalytic materials in the electrocatalyst, the nanoporous alloy catalytic layer and electroplating alloy catalytic layer are formed layer by layer, which solves the problems of high energy barrier and low catalytic activity of existing electrocatalysts when catalyzing water to decompose hydrogen under high current density, and achieves efficient and stable hydrogen production and large-scale industrial application.
Patent Information
- Application Number
- CN202411894201.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-05-02
AI Technical Summary
When existing electrocatalysts catalyze water to decompose hydrogen under high current density, there are problems such as high energy barrier, low catalytic activity and difficulty in large-scale production.
Using nanoporous composite electrocatalytic materials, nanoporous alloy catalytic layer and electroplating alloy catalytic layer are formed layer by layer, and the nanoporous structure is used to accelerate electrolyte penetration and gas diffusion, thereby improving catalytic activity and stability.
At high current density, the energy consumption of water decomposed hydrogen is significantly reduced, catalytic activity and long-term stability are improved, and large-scale industrial applications are achieved.
Smart Images

Figure CN119913551A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochemical materials, and in particular to a nanoporous composite electrocatalytic material and a preparation method and application thereof. Background Art
[0002] Hydrogen is one of the most promising clean energy sources due to its advantages such as high energy density and cleanliness. Electrocatalytic water splitting is an environmentally friendly method to produce high-purity hydrogen. It is of great significance in dealing with the energy crisis caused by the gradual depletion of fossil fuels and environmental pollution caused by excessive carbon emissions. However, due to the slow kinetics of the cathode half-reaction of water splitting, namely the hydrogen evolution reaction (HER), a high energy barrier needs to be overcome when splitting water, resulting in high energy consumption in the water electrolysis process. In order to reduce the high energy barrier of HER, platinum-based, ruthenium-based and other precious metal electrocatalysts have been used as efficient catalysts for HER, but the scarcity and high cost of precious metals limit their large-scale application. Therefore, it is critical to develop HER catalysts with excellent performance and low price. In recent years, in order to reduce the manufacturing cost of catalysts for hydrogen production by water electrolysis, various non-precious metals and their composite materials have been prepared as cathode catalysts. However, many existing catalysts are often below 100 mA cm at current density. -2 , and its hydrogen evolution overpotential is still high, and the hydrogen evolution catalytic activity needs to be improved, especially at high current density, which cannot meet the needs of industrial production.
[0003] In addition, many existing catalysts are difficult to apply to large-area electrodes due to limitations in scale-up and macroscopic mass manufacturing methods, making it impossible to evaluate their performance in actual industrial water-splitting electrolyzers. Therefore, multifunctional catalyst systems that can be effectively applied under industrial conditions (with high current density, high activity, high stability and easy scalability) are crucial to promote hydrogen energy from basic applications to practical applications. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a nanoporous composite electrocatalytic material, including a nanoporous alloy catalytic layer and an electroplated alloy catalytic layer formed layer by layer, the nanoporous alloy catalytic layer includes a metal substrate and a nanoporous structure, the nanoporous structure is formed on the surface of the metal substrate, and the electroplated alloy catalytic layer is formed on the surface of the nanoporous structure by electroplating.
[0005] Optionally, the nanoporous structure is formed by subjecting an alloy layer formed on the surface of the metal substrate by alloying to a dealloying process.
[0006] Optionally, the metal substrate includes a first metal or a first metal alloy, and the alloy layer includes the first metal and a second metal or a second metal alloy.
[0007] Optionally, the first metal includes at least one of nickel, cobalt, copper, and iron, and the second metal includes at least one of zinc, aluminum, manganese, magnesium, and molybdenum.
[0008] Optionally, the dealloying process includes a gas phase dealloying method or a liquid phase chemical dealloying method.
[0009] Optionally, the thickness of the nanoporous alloy catalyst layer is 3 μm to 40 μm; the average pore size of the pores in the nanoporous structure is 3 nm to 650 nm, and the ligament size range in the nanoporous metal substrate layer is 100 nm to 2.5 μm.
[0010] Optionally, the electroplated alloy catalyst layer includes an alloy composed of two or more different metal elements.
[0011] Optionally, the alloy composed of two or more different metal elements includes at least two of nickel, cobalt, molybdenum, iron, tungsten, copper, zinc, aluminum, and tantalum.
[0012] Optionally, the nanoporous composite electrocatalytic material is used as a cathode catalyst for hydrogen production by alkaline water electrolysis.
[0013] The present invention also provides a method for preparing a nanoporous composite electrocatalytic material, comprising the following steps:
[0014] S1, covering the surface of a metal substrate with a mixture of metal powder and filler, and forming an alloy layer on the surface of the metal substrate by alloying treatment;
[0015] S2, the alloy layer is treated by a dealloying process to form a nanoporous structure on the surface of the metal substrate, and the metal substrate and the nanoporous structure on its surface form a nanoporous alloy catalyst layer;
[0016] S3, placing the formed nanoporous alloy catalyst layer in an electroplating solution, and forming an electroplated alloy catalyst layer on the surface of the nanoporous structure by electroplating.
[0017] Optionally, the metal powder includes at least one of zinc powder, aluminum powder, manganese powder, magnesium powder and molybdenum powder; and the filler is alumina or quartz sand.
[0018] Optionally, step S1 includes the following steps:
[0019] S11, mixing the metal powder and the filler to form the mixture;
[0020] S12, placing the metal substrate in an alloying device, and covering the surface of the metal substrate with the mixture, and introducing a protective gas into the alloying device for 15 min to 30 min;
[0021] S13. After introducing protective gas into the alloy layering equipment for 15 minutes to 30 minutes, the metal substrate covering the mixture is annealed to form the alloy layer on the surface of the metal substrate; wherein the annealing temperature is 300°C to 1000°C, and the annealing time is 0.1h to 5h.
[0022] Optionally, in step S2, the dealloying process adopts a gas phase dealloying method, and the gas phase dealloying method includes:
[0023] The metal substrate with the alloy layer formed on the surface is placed in a heat treatment furnace for heating, and the alloy layer is decomposed by heating to form the nanoporous structure; wherein the pressure range of the heat treatment furnace is 10 -3 Pa~10 5 Pa, the heating temperature is 450℃~850℃, and the heating time is 0.5h~3.5h.
[0024] Optionally, in step S2, the dealloying process adopts a liquid phase chemical dealloying method, and the liquid phase chemical dealloying method includes:
[0025] The metal substrate with the alloy layer formed on the surface is placed in a chemical etching solution, and at a certain etching temperature and etching time, the alloy layer is chemically etched and dealloyed to form the nanoporous structure;
[0026] Wherein, the chemical etching solution includes at least one of potassium hydroxide solution, sodium hydroxide solution, sodium carbonate solution, potassium carbonate solution, sodium bicarbonate solution, potassium bicarbonate solution, sodium phosphate solution, sodium monohydrogen phosphate solution, sodium dihydrogen phosphate solution, potassium phosphate solution, potassium monohydrogen phosphate solution, potassium dihydrogen phosphate solution, hydrochloric acid solution, sulfuric acid solution, nitric acid solution, phosphoric acid solution, ammonium chloride solution, ammonium sulfate solution, ammonium nitrate solution, ammonium carbonate solution, ammonium bicarbonate solution, ammonium phosphate solution, ammonium monohydrogen phosphate solution, and diammonium phosphate solution, the concentration of the chemical etching solution is 0.1M~6M, the etching time is 0.1h~12h, and the etching temperature is 10℃~80℃.
[0027] Optionally, in step S3, the cleaned nanoporous alloy catalyst layer is placed in a chemical plating solution for electroplating using a hanger;
[0028] The concentration of all solutes in the electroplating solution is 0.01M to 2M, and the electroplating time is between 1min and 60min. The electroplating method is three-electrode constant voltage electroplating or two-electrode constant current electroplating. When the electroplating method is three-electrode constant voltage electroplating, the reference electrode is an Ag / AgCl electrode, the counter electrode is a carbon rod, and the deposition potential is -1V to -2V; when the electroplating method is two-electrode constant current electroplating, the electroplating current density is 5mA cm -2 ~1000mA cm -2 ; The temperature of the electroplating solution is 10°C to 60°C; the electroplating anode is a metal plate having an area larger than that of the nanoporous alloy catalyst layer; and the hanger is a copper hanger or a titanium hanger.
[0029] Optionally, in step S3, the electroplated alloy catalyst layer includes at least two metal elements selected from the group consisting of nickel, cobalt, molybdenum, iron, tungsten, copper, zinc, aluminum, and tantalum.
[0030] Optionally, in step S3, if the electroplated alloy catalyst layer includes metallic nickel, the electroplating solution includes a nickel salt, and the nickel salt includes at least one of nickel chloride, nickel sulfate, nickel nitrite, nickel nitrate, nickel hydroxide, nickel acetate, nickel sulfamate, and nickel bromide;
[0031] If the electroplating alloy catalyst layer includes metallic cobalt, the electroplating solution includes a cobalt salt, and the cobalt salt includes at least one of cobalt chloride, cobalt oxalate, cobalt carbonate, cobalt sulfate, cobalt nitrate, and cobalt acetate.
[0032] If the electroplated alloy catalyst layer includes metal molybdenum, the electroplating solution includes a molybdenum salt, and the molybdenum salt includes at least one of sodium molybdate, ammonium molybdate, ammonium dimolybdate, ammonium tetramolybdate, potassium molybdate, magnesium molybdate and zinc molybdate;
[0033] If the electroplating alloy catalyst layer includes metallic iron, the electroplating solution includes ferrous salt, and the ferrous salt includes at least one of ferrous chloride, ferrous sulfate, ferrous nitrate, and ferrous bromide.
[0034] Optionally, in step S3, the electroplating solution further contains an additive, and the additive includes at least one of sodium citrate, sodium tartrate, sodium chloride, potassium chloride, sodium nitrate, sodium sulfate, potassium sulfate, and potassium nitrate.
[0035] Optionally, in step S3, the electroplating solution further comprises a pH adjuster, and the pH adjuster includes at least one of potassium hydroxide solution, hydrochloric acid solution, sodium hydroxide solution, sulfuric acid solution, ammonia solution, sodium carbonate, and sodium bicarbonate.
[0036] Optionally, the pH value of the electroplating solution is 7-11.
[0037] Compared with the prior art, the technical solution of the embodiment of the present invention has the following beneficial effects:
[0038] At high current density, HER performance is controlled by reaction kinetics and mass transfer processes. Rapid catalytic reactions at high current density lead to rapid consumption of the plating solution and the generation of a large number of H2 bubbles, requiring rapid supply of electrolyte and rapid discharge of bubbles. The present invention can accelerate the penetration of electrolyte and the diffusion of H2 bubbles through a nanoporous structure with an open framework, thereby ensuring the mass transfer efficiency and gas diffusion rate in the HER process at high current.
[0039] Furthermore, since the nanoporous structure formed in the nanoporous composite electrocatalyst material of the present invention is only produced in the alloy layer on the surface of the metal substrate, the strong mechanical contact between it and the metal substrate of the conductive substrate can effectively prevent the active material from falling off, which also ensures the stability and activity of the formed nanoporous composite electrocatalyst material.
[0040] In addition, in the present invention, the nanoporous structure formed by dealloying has a large specific surface area, which can provide more active sites for the electrocatalytic hydrogen evolution reaction, thereby improving the catalytic hydrogen evolution activity. The nickel-molybdenum alloy contained in the electroplated alloy catalyst layer has a high HER catalytic activity, which can further reduce the energy barrier of the hydrogen evolution reaction kinetics, thereby reducing the overpotential of the hydrogen evolution reaction. The nanoporous composite electrocatalytic material can effectively reduce energy consumption and improve energy utilization efficiency when producing hydrogen under industrial high current density, and can realize large-scale industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0042] Figure 1 A scanning electron microscope image of a nanoporous alloy catalyst layer prepared by the method for preparing a nanoporous composite electrocatalytic material provided in Example 1 of the present invention;
[0043] Figure 2 A scanning electron microscope image of a nanoporous composite electrocatalyst material comprising a nanoporous alloy catalyst layer and an electroplated alloy catalyst layer, obtained by the method for preparing a nanoporous composite electrocatalyst material provided in Example 1 of the present invention;
[0044] Figure 3a to Figure 3d An energy spectrum analysis diagram of a nanoporous composite electrocatalyst material prepared by the method for preparing a nanoporous composite electrocatalyst material provided in Example 1 of the present invention;
[0045] Figure 4 A graph showing the hydrogen evolution performance of the cathode of alkaline water electrolysis of the nanoporous composite electrocatalyst material prepared by the method for preparing the nanoporous composite electrocatalyst material provided in Examples 1 and 2 of the present invention;
[0046] Figure 5 This is a graph showing the long-term stability performance of the alkaline water electrolysis cathode hydrogen evolution catalysis of the nanoporous composite electrocatalyst material prepared by the method for preparing the nanoporous composite electrocatalyst material provided in Example 2 of the present invention. DETAILED DESCRIPTION
[0047] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] The terms "first", "second", "third", "fourth", etc. (if any) in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0049] Electrocatalytic water splitting is an environmentally friendly method for producing high-purity hydrogen. It is of great significance in addressing the energy crisis caused by the gradual depletion of fossil fuels and the environmental pollution caused by excessive carbon emissions. However, due to the slow kinetics of the cathode half-reaction of water splitting, namely the hydrogen evolution reaction (HER), a high energy barrier needs to be overcome when splitting water, resulting in high energy consumption in the water electrolysis process. In order to reduce the high energy barrier of HER, platinum-based, ruthenium-based and other precious metal electrocatalysts have been used as efficient catalysts for HER, but the scarcity and high cost of precious metals limit their large-scale application. Therefore, it is critical to develop HER catalysts with excellent performance and low price. In recent years, in order to reduce the manufacturing cost of catalysts for hydrogen production by water electrolysis, various non-precious metals and their composite materials have been prepared as cathode catalysts. However, many existing catalysts are often below 100mA cm at current density. -2, and its hydrogen evolution overpotential is still high, and the hydrogen evolution catalytic activity needs to be improved, especially at high current density, which cannot meet the needs of industrial production.
[0050] In order to achieve the performance requirements of the cathode catalyst in an actual industrial water splitting electrolyzer, the inventors of the present application conducted a series of studies: Considering that the rapid catalytic reaction under high current density will lead to rapid consumption of the electrolyte and the generation of a large number of H2 bubbles, it is necessary to solve the problem of rapid supply of electrolyte and rapid discharge of bubbles.
[0051] In order to solve the above problems, the present invention provides a nanoporous composite electrocatalytic material, which includes a nanoporous alloy catalyst layer and an electroplated alloy catalyst layer formed layer by layer, the nanoporous alloy catalyst layer includes a metal substrate and a nanoporous structure, the nanoporous structure is formed on the surface of the metal substrate, and the electroplated alloy catalyst layer is formed on the surface of the nanoporous structure by electroplating; the electroplated alloy catalyst layer and the nanoporous structure are strongly combined to increase the bonding strength and structural stability. The nanoporous composite electrocatalytic material provided by the present invention improves the electronic structure through the uniformly dispersed nanoporous structure formed, optimizes the mass transfer efficiency and gas diffusion rate of the catalytic process, so that the cathode catalyst has high activity and long-term stability under high current density, and can achieve large-scale industrial application.
[0052] The metal substrate is active for electrolyzing water. The metal substrate comprises a first metal or a first metal alloy. As for whether the metal substrate is the first metal or the first metal alloy, the present invention does not make any specific restrictions on this, as long as the metal substrate contains the first metal element.
[0053] As an embodiment, the first metal includes at least one of nickel, cobalt, copper and iron. These metals have corresponding catalytic activity for electrocatalytic water decomposition reaction and are suitable as elements for synthesizing nanoporous structures.
[0054] The present invention does not limit the specific preparation method of the nanoporous structure. As an embodiment, the nanoporous structure is formed by an alloy layer formed on the surface of the metal substrate by alloying and then subjected to a dealloying process. Of course, the nanoporous structure of the present invention is not limited to being formed by an alloy layer formed on the surface of the metal substrate by alloying and then subjected to a dealloying process, and can also be formed by a template method, etc.
[0055] Taking the example that the nanoporous structure is formed by alloying an alloy layer on the surface of the metal substrate and then subjected to a dealloying process, the alloy layer is formed by alloying a second metal or a second metal alloy on the surface of the metal substrate, and therefore, the alloy layer includes a first metal and a second metal or a second metal alloy.
[0056] The present invention does not limit the specific composition of the second metal. For example, the second metal includes at least one of zinc, aluminum, manganese, magnesium, and molybdenum. These metals have corresponding catalytic activity for the electrocatalytic decomposition of water and are suitable as elements for synthesizing nanoporous structures.
[0057] The alloy layer is dealloyed to form a nanoporous structure, that is, the nanoporous structure is only generated in the alloy layer on the surface of the metal substrate, and the strong mechanical contact between the alloy layer and the conductive substrate metal substrate can effectively prevent the active material from falling off.
[0058] The electroplated alloy catalyst layer includes an alloy composed of two or more different metal elements. The present invention does not impose any specific restrictions on the two or more metal elements. For example, the two or more metal elements may be at least two of nickel, cobalt, molybdenum, iron, tungsten, copper, zinc, aluminum, and tantalum. The active metal components of the electroplated alloy catalyst layer can further reduce the thermodynamic barrier of electrocatalytic hydrogen production and provide more catalytic active sites.
[0059] The present invention can accelerate the penetration of electrolyte and the diffusion of H2 bubbles through the nanoporous alloy catalyst layer with an open frame, thereby ensuring the mass transfer efficiency and gas diffusion rate in the HER process under high current. At the same time, the strong mechanical contact between the nanoporous structure and the metal base of the conductive substrate can effectively prevent the active material from falling off, thereby ensuring long-term stability.
[0060] The present invention also provides a method for preparing a nanoporous composite electrocatalytic material, comprising the following steps:
[0061] S1, covering the surface of a metal substrate with a mixture of metal powder and filler, and forming an alloy layer on the surface of the metal substrate by alloying treatment;
[0062] S2, the alloy layer is treated by a dealloying process to form a nanoporous structure on the surface of the metal substrate, and the metal substrate and the nanoporous structure on its surface form a nanoporous alloy catalyst layer;
[0063] S3, placing the formed nanoporous alloy catalyst layer in an electroplating solution, and forming an electroplated alloy catalyst layer on the surface of the nanoporous structure by electroplating. Therefore, the nanoporous alloy catalyst layer and the electroplated alloy catalyst layer form a nanoporous composite electrocatalytic material.
[0064] The present invention alloys a mixture of a metal substrate, metal powder and a filler in an alloying device to form an alloy layer on the surface of the metal substrate; the metal substrate with the alloy layer formed on the surface is dealloyed to form a nanoporous alloy catalytic layer; the nanoporous alloy catalytic layer is placed in an electroplating solution and electroplated on the surface to form an electroplated alloy catalytic layer.
[0065] As an embodiment, the alloying process can adjust the thickness of the alloy layer by specifically controlling the types and mixing ratios of the raw material metal powder and the filler, and controlling the heating temperature and reaction time during the alloying process, thereby optimizing the formation mode of the subsequent dealloying process and the bonding strength between the nanoporous structure and the metal substrate.
[0066] Since the nanoporous structure formed in the nanoporous composite electrocatalyst material prepared in the present invention is only produced in the alloy layer on the surface of the metal substrate, the strong mechanical contact between it and the metal substrate of the conductive substrate can effectively prevent the active material from falling off, which also ensures the stability and activity of the formed nanoporous composite electrocatalyst material.
[0067] The present invention does not specifically limit the dealloying treatment method of the alloy layer. For example, the alloy layer can be formed into a nanoporous structure on the surface of the metal substrate by a dealloying treatment method such as a gas phase dealloying method, a liquid phase chemical dealloying method, or mechanical processing. As for whether the alloy layer is completely free of metal materials, the present invention does not limit this, as long as the alloy layer can form a nanoporous structure after the dealloying treatment.
[0068] As an embodiment, the gas phase dealloying method can adjust the pore size of the nanoporous structure by specifically controlling the pressure, heating temperature and reaction time during the process, so that the formed nanoporous composite electrocatalytic material can have a small pore size and high porosity.
[0069] As another embodiment, the liquid phase chemical dealloying process can also adjust the pore size of the nanoporous structure by specifically controlling the selection of chemical etching reagents, etching temperature, and etching time in the process. At the same time, since high-temperature treatment is avoided, the coarsening of metal ligaments is effectively prevented, so that the formed nanoporous composite electrocatalytic material can have a nanoscale pore size.
[0070] Furthermore, in the present invention, the thickness of the electroplated alloy catalyst layer can be controlled by specifically regulating the electroplating time and the electroplating current. The strong combination between the electroplated alloy catalyst layer and the nanoporous alloy catalyst layer increases the bonding strength and structural stability; at the same time, the electroplated alloy catalyst layer can fill the cracks formed by the shrinkage of the alloy layer during the dealloying process, further enhancing the stability of the formed nanoporous composite electrocatalytic material. The nanoporous structure of the nanoporous alloy catalyst layer can accelerate the penetration of the electrolyte and the diffusion of H2 bubbles, thereby ensuring the mass transfer efficiency and gas diffusion rate in the HER process under high current, and at the same time, its large specific surface area can provide more active sites for the electrocatalytic hydrogen evolution reaction; the alloy composed of two or more different metal elements contained in the electroplated alloy catalyst layer has a high HER catalytic activity, which can further reduce the energy barrier of the hydrogen evolution reaction kinetics, thereby reducing the overpotential of the hydrogen evolution reaction. This composite electrocatalytic material can effectively reduce energy consumption and improve energy utilization efficiency when producing hydrogen under industrial high current density, and can realize large-scale industrial application.
[0071] In order to make the above-mentioned purposes, features and beneficial effects of the present invention more obvious and understandable, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0072] The present invention provides a method for preparing a nanoporous composite electrocatalytic material, comprising the following steps:
[0073] 1. Preparation of metal base alloy layer
[0074] The preparation of the metal substrate alloy layer specifically includes:
[0075] S1, covering the surface of a metal substrate with a mixture of metal powder and filler, and forming an alloy layer on the surface of the metal substrate by alloying treatment;
[0076] The metal substrate is active for electrolysis of water. As to whether the metal substrate is a metal or a metal alloy, the present invention does not specifically limit this, as long as the metal substrate contains metal elements. As an embodiment, the metal substrate includes a first metal or a first metal alloy, and the first metal includes at least one of nickel, cobalt, copper, and iron. These metals have corresponding catalytic activity for electrocatalytic water decomposition reaction and are suitable as elements for synthesizing nanoporous structures.
[0077] The metal powder includes at least one of zinc powder, aluminum powder, manganese powder, magnesium powder and molybdenum powder. These metals have corresponding catalytic activity for electrocatalytic water decomposition reaction and are suitable as elements for synthesizing nanoporous structures.
[0078] The filler has the following two functions:
[0079] First, the amount of metal powder can be reduced. Using less metal powder and filler can achieve the same embedding volume, thus achieving the purpose of reducing costs.
[0080] Secondly, the thermal diffusion rate can be slowed down by reducing the contact probability between the metal powder and the metal substrate, preventing the thermal diffusion rate from being too fast and causing the alloy layer to be too thick. Since an overly thick nanoporous structure has a high probability of falling off, controlling the thickness of the nanoporous structure can prevent it from falling off and causing a decrease in catalytic activity.
[0081] The filler may be alumina or quartz sand.
[0082] The alloying process requires filling with protective gas, and the protective gas includes at least one of nitrogen, helium, neon, argon, xenon, and hydrogen.
[0083] 2. Preparation of Nanoporous Alloy Catalytic Layer
[0084] The preparation of the nanoporous alloy catalyst layer specifically includes:
[0085] S2. The alloy layer is treated by a dealloying process to form a nanoporous structure on the surface of the metal substrate. The metal substrate and the nanoporous structure on its surface form a nanoporous alloy catalyst layer.
[0086] The dealloying process includes dealloying methods such as gas phase dealloying method, liquid phase chemical dealloying method or mechanical processing. The present invention does not limit whether the alloy layer is completely free of metal materials, as long as the alloy layer can form a nanoporous structure after the dealloying treatment.
[0087] 3. Preparation of electroplated alloy catalyst layer
[0088] The preparation of the electroplated alloy catalyst layer specifically includes:
[0089] S3, further placing the formed nanoporous alloy catalyst layer in a prepared electroplating solution, forming an electroplated alloy catalyst layer on the surface of the nanoporous alloy catalyst layer by electroplating, and the electroplated alloy catalyst layer is distributed on the surface of the nanoporous structure.
[0090] The electroplated alloy catalyst layer includes an alloy composed of two or more different metal elements, including at least two of nickel, cobalt, molybdenum, iron, tungsten, copper, zinc, aluminum, and tantalum.
[0091] If the electroplating alloy catalyst layer includes metallic nickel, the electroplating solution includes a nickel salt, and the nickel salt includes at least one of nickel chloride (NiCl2), nickel sulfate (NiSO4), nickel nitrite (Ni(NO2)2), nickel nitrate (Ni(NO3)2), nickel hydroxide (Ni(OH)2), nickel acetate, nickel sulfamate, and nickel bromide. The molar concentration of the nickel salt is 0.2-0.6M.
[0092] If the electroplated alloy catalyst layer includes metal cobalt, the electroplating solution includes a cobalt salt, and the cobalt salt includes at least one of cobalt chloride, cobalt oxalate, cobalt carbonate, cobalt sulfate, cobalt nitrate, and cobalt acetate. The molar concentration of the cobalt salt is 0.1-0.3M.
[0093] If the electroplating alloy catalyst layer includes metallic molybdenum, the electroplating solution includes a molybdenum salt, and the molybdenum salt includes at least one of sodium molybdate, ammonium molybdate, ammonium dimolybdate ((NH4)2Mo2O7), ammonium tetramolybdate, potassium molybdate, magnesium molybdate and zinc molybdate. The molar concentration of the molybdenum salt is 0.03-0.5M
[0094] If the electroplating alloy catalyst layer includes metallic iron, the electroplating solution includes ferrous salt, and the ferrous salt includes at least one of ferrous chloride, ferrous sulfate, ferrous nitrate, and ferrous bromide. The molar concentration of the ferrous salt is 0.1-0.5M.
[0095] Furthermore, the electroplating solution further contains an additive, and the additive includes at least one of sodium citrate, sodium tartrate, sodium chloride, potassium chloride, sodium nitrate, sodium sulfate, potassium sulfate, and potassium nitrate. The molar concentration of the additive is 0.1-0.6M.
[0096] The electroplating solution further comprises a pH regulator, which includes at least one of potassium hydroxide solution, hydrochloric acid solution, sodium hydroxide solution, sulfuric acid solution, ammonia solution, sodium carbonate, and sodium bicarbonate. The pH of the electroplating solution is 7-11.
[0097] The nanoporous composite electrocatalytic material prepared by the above-mentioned preparation method includes a nanoporous alloy catalytic layer and an electroplated alloy catalytic layer formed layer by layer, wherein the nanoporous alloy catalytic layer includes a metal substrate and a nanoporous structure, wherein the nanoporous structure is formed on the surface of the metal substrate, wherein the nanoporous structure is formed by alloying an alloy layer formed on the surface of the metal substrate and then subjected to a dealloying process; the electroplated alloy catalytic layer is formed on the surface of the nanoporous structure by electroplating; and the electroplated alloy catalytic layer and the nanoporous structure layer are strongly bonded.
[0098] In one embodiment, the specific steps of step S1 of preparing the metal substrate include:
[0099] S101, mixing metal powder and filler to form a mixture;
[0100] The present invention does not limit the specific types of metal powder and filler in the mixture. As a specific embodiment, the metal powder can be one of zinc powder, aluminum powder, manganese powder, magnesium powder, and molybdenum powder, wherein the particle size of the metal powder is 120 mesh to 325 mesh.
[0101] The filler may be alumina or quartz sand, wherein the particle size of the filler is 40 mesh to 325 mesh.
[0102] The metal substrate takes a nickel substrate as an example. The present invention does not specifically limit the shape of the nickel substrate, which can be a mesh, foam or felt. If the nickel substrate is a mesh or foam, the mesh number of the nickel substrate is 10 to 110 meshes; if the nickel substrate is a felt, the wire diameter of the nickel substrate is in the range of 3 μm to 100 μm.
[0103] In this step, the metal powder and the filler are uniformly mixed in a certain mass ratio, such as a ratio of 1: 1. Of course, the mass ratio of the metal powder to the filler in the present invention is not limited to a ratio of 1: 1, and other ratios can be set according to actual use requirements.
[0104] S102, placing a metal substrate in an alloying device, and covering the surface of the metal substrate with the mixture;
[0105] In this step, the metal substrate is placed in an alloying device, which is a high-temperature device such as a tube furnace, and the mixture is completely covered on the surface of the metal substrate, so that the surface of the metal substrate is not exposed.
[0106] S103. In an alloying device, the metal substrate covered with the mixture is annealed to form the alloy layer on the surface of the metal substrate; wherein the annealing temperature is 300° C. to 1000° C. and the annealing time is 0.1 h to 5 h.
[0107] In this step, argon is selected as the protective gas. After argon is continuously introduced into the tube furnace for a period of time, the metal substrate covered with the mixture is heated in the tube furnace at a temperature of 300°C to 1000°C for a holding time of 0.1h to 5h. In a specific embodiment, after argon is continuously introduced into the tube furnace for 30 minutes, the metal substrate covered with the mixture is heated in the tube furnace at a temperature of 400°C for a holding time of 0.5h.
[0108] In this embodiment, the thickness of the alloy layer can be controlled by specifically regulating the thickness of the mixture, the temperature in the tube furnace and / or the insulation time. For example, the thickness of the alloy layer is 3 μm to 40 μm.
[0109] In one embodiment, the specific steps of step S2 of preparing the nanoporous alloy catalyst layer include:
[0110] S201, after the alloy layer is formed on the surface of the metal substrate, separating the cooled metal substrate with the alloy layer formed thereon from the powder of the mixture and cleaning the residual powder on the surface;
[0111] S202, using a liquid phase chemical dealloying method, placing the metal substrate with the alloy layer formed on the surface into a chemical etching solution, and the alloy layer is dealloyed by chemical etching to form the nanoporous structure.
[0112] Wherein, the chemical etching solution includes at least one of potassium hydroxide solution, sodium hydroxide solution, sodium carbonate solution, potassium carbonate solution, sodium bicarbonate solution, potassium bicarbonate solution, sodium phosphate solution, sodium monohydrogen phosphate solution, sodium dihydrogen phosphate solution, potassium phosphate solution, potassium monohydrogen phosphate solution, potassium dihydrogen phosphate solution, hydrochloric acid solution, sulfuric acid solution, nitric acid solution, phosphoric acid solution, ammonium chloride solution, ammonium sulfate solution, ammonium nitrate solution, ammonium carbonate solution, ammonium bicarbonate solution, ammonium phosphate solution, ammonium monohydrogen phosphate solution, and diammonium phosphate solution; the concentration of the chemical etching solution is 0.1M~6M, the etching time is 0.1h~12h, and the etching temperature is 10℃~80℃.
[0113] This embodiment can control the pore size and ligament size of the resulting nanoporous layer by specifically regulating the dealloying method type, dealloying insulation temperature, vacuum degree, insulation time or etchant type, etchant concentration, etching temperature, and etching time to obtain a suitable nanoporous alloy catalyst layer with the highest catalytic activity.
[0114] As an embodiment, the average pore diameter of the plurality of pores in the nanoporous structure is 3 nm to 650 nm, and the size range of the ligaments in the nanoporous metal substrate is 100 nm to 2.5 μm.
[0115] In one embodiment, the specific steps of step S3 of preparing the electroplated alloy catalyst layer include:
[0116] S301, in the early stage of electroplating, the nanoporous alloy catalyst layer is cleaned with pure water, degreased, pickled to remove oxide scale, acid-dipped to activate, and dried;
[0117] In this step, the impurities on the surface of the nanoporous alloy catalyst layer having the nanoporous structure formed on the surface are cleaned and activated to facilitate electroplating.
[0118] S302, placing the cleaned nanoporous alloy catalyst layer into a chemical electroplating solution for electroplating using a hanger; wherein the metal salt component of the electroplating solution includes two or more of cobalt sulfate, cobalt chloride, cobalt oxalate, cobalt carbonate, cobalt nitrate, cobalt acetate, sodium molybdate, ammonium molybdate, ammonium dimolybdate ((NH4)2Mo2O7), ammonium tetramolybdate, potassium molybdate, magnesium molybdate, zinc molybdate, nickel chloride (NiCl2), nickel sulfate (NiSO4), nickel nitrite (Ni(NO2)2), nickel nitrate (Ni(NO3)2), nickel hydroxide (Ni(OH)2), nickel acetate, nickel sulfamate, nickel bromide, ferrous chloride, ferrous sulfate, ferrous nitrate, and ferrous bromide; the pH adjuster and additive components in the electroplating solution include at least two of potassium hydroxide solution, hydrochloric acid, sodium hydroxide solution, sulfuric acid, ammonia solution, sodium carbonate, sodium bicarbonate, sodium citrate, sodium tartrate, sodium chloride, potassium chloride, sodium nitrate (NaNO3), sodium sulfate, potassium sulfate, and potassium nitrate;
[0119] In this step, the concentration of all solutes in the electroplating solution is 0.01M to 2M, and the electroplating time is between 1min and 60min; the electroplating method is three-electrode constant voltage electroplating or two-electrode constant current electroplating. When the electroplating method is three-electrode constant voltage electroplating, the reference electrode is an Ag / AgCl electrode, the counter electrode is a carbon rod, and the deposition potential is -1V to -2V; when the electroplating method is two-electrode constant current electroplating, the electroplating current density is 5mA cm -2 ~1000mA cm -2 ; The temperature of the electroplating solution is 10°C to 60°C; the electroplating anode is a metal plate having an area larger than that of the nanoporous alloy catalyst layer; and the hanger is a copper hanger or a titanium hanger.
[0120] In this embodiment, the thickness of the electroplated alloy catalyst layer can be controlled by specifically regulating the electroplating time and the electroplating current, thereby obtaining a suitable electroplated alloy catalyst layer with the highest catalytic activity.
[0121] The nanoporous composite electrocatalytic material prepared by the method of the present invention comprises a nanoporous alloy catalytic layer and an electroplated alloy catalytic layer formed layer by layer, wherein the nanoporous alloy catalytic layer comprises a metal substrate and a nanoporous structure, and the electroplated alloy catalytic layer is formed on the surface of the nanoporous structure by electroplating and is strongly bonded, thereby increasing the bonding strength and structural stability. The nanoporous structure of the nanoporous alloy catalytic layer can accelerate the penetration of the electrolyte and the diffusion of H2 bubbles, thereby ensuring the mass transfer efficiency and gas diffusion rate in the HER process under high current, and at the same time, its large specific surface area can provide more active sites for the electrocatalytic hydrogen evolution reaction; the nickel-molybdenum alloy contained in the electroplated alloy catalytic layer has a high HER catalytic activity, which can further reduce the energy barrier of the hydrogen evolution reaction kinetics, thereby reducing the overpotential of the hydrogen evolution reaction. This composite electrocatalytic material can effectively reduce energy consumption and improve energy utilization efficiency when producing hydrogen under industrial high current density, and can realize large-scale industrial application.
[0122] The present invention also provides an application of a nanoporous composite electrocatalytic material, wherein the nanoporous composite electrocatalytic material is used as a cathode catalyst for hydrogen production by alkaline water electrolysis.
[0123] When the nanoporous composite electrocatalytic material of the present invention is used as a cathode catalyst for alkaline water electrolysis in an electrolytic cell, the water electrolysis efficiency can be greatly improved, a lower voltage is required to achieve the same current density, and a greater gas output can be obtained with lower energy consumption.
[0124] The nanoporous composite electrocatalytic material provided by the present invention can be used not only as a cathode catalyst for hydrogen production in alkaline water electrolysis, but also as an anode catalyst for oxygen production in alkaline water electrolysis. When the nanoporous composite electrocatalytic material is used as an anode catalyst for alkaline water electrolysis in an electrolyzer, it can greatly improve the efficiency of water electrolysis, requiring a lower voltage to achieve the same current density, and can obtain a greater gas output with lower energy consumption.
[0125] The following is a detailed description of the preparation method of the nanoporous composite electrocatalyst material of the present invention with several specific embodiments. The sources of raw materials, equipment and equipment operation involved in the following method of preparing the nanoporous composite electrocatalyst material are well known to those skilled in the art and will not be described in detail here.
[0126] Example 1
[0127] Before preparing the nanoporous composite electrocatalytic material, the following raw materials need to be prepared: the metal substrate is a nickel substrate, the shape of the nickel substrate is a mesh, and the mesh size is 50 mesh; the metal powder is metal Zn, the shape of which is powder, and the particle size is 325 mesh; the filler is alumina, the shape of which is powder, and the particle size is 325 mesh.
[0128] The method for preparing the nanoporous composite electrocatalytic material described in Example 1 specifically comprises:
[0129] S11, mixing zinc powder and aluminum oxide powder to form a mixture;
[0130] S12, placing a mesh nickel substrate into a tube furnace, and uniformly mixing Zn powder and Al2O3 powder in a mass ratio of 1:1, and then covering the surface of the nickel substrate to ensure that the surface of the nickel substrate is not exposed;
[0131] S13, selecting argon as a protective gas, and after continuously introducing argon into the tube furnace for 30 minutes, heating the nickel substrate covered with the mixed powder in the tube furnace at a temperature of 400° C. for a heat preservation time of 0.5 hours, to form an alloy layer on the surface of the nickel substrate;
[0132] S14, after the surface alloying of the nickel substrate is completed, the cooled nickel substrate is separated from the mixed powder and the residual powder on the surface is cleaned;
[0133] S15. Place the cleaned nickel substrate in a vacuum heat treatment furnace and heat it at a pressure of 50 Pa, a temperature of 450° C., and a heat preservation time of 3 hours to form a nanoporous structure on the surface of the nickel substrate. The nickel substrate and the nanoporous structure on its surface form a nanoporous alloy catalyst layer.
[0134] S16. The nanoporous alloy catalyst layer with a nanoporous structure formed on the surface is subjected to pure water cleaning, oil removal, acid washing to remove oxide scale, acid immersion activation and drying treatment. First, ultrasonic cleaning with deionized water is performed for 5 minutes; the nanoporous alloy catalyst layer is placed in a degreasing agent containing 15g / L sodium hydroxide, 20g / L sodium carbonate and 6.47g / L sodium phosphate at a temperature of 40°C for 20 minutes; the nanoporous alloy catalyst layer is washed with warm water at 60°C; the nanoporous alloy catalyst layer is washed with cold water at 25°C; the nanoporous alloy catalyst layer is immersed in a 2M HCl solution at room temperature for activation for 5 minutes; the nanoporous alloy catalyst layer is washed with cold water at 25°C.
[0135] S17, using a copper hanger, place the cleaned nanoporous alloy catalyst layer into an electroplating solution containing 0.32M ammonium molybdate, 0.23M nickel sulfate, 0.41M sodium citrate, 0.17M sodium chloride, and 100ml / L ammonia water, adjust the pH to 9.6 with hydrochloric acid solution and sodium hydroxide solution, use a copper plate with a larger area than the nanoporous alloy catalyst layer as the electroplating anode, select two-electrode constant current electroplating, and adjust the electroplating current density to 500mA cm -2 , the electroplating time is 15min.
[0136] The nanoporous composite electrocatalytic material provided in this embodiment includes a nanoporous alloy catalyst layer and an electroplated alloy catalyst layer. The nanoporous structure of the nanoporous alloy catalyst layer can accelerate the penetration of electrolytes and the diffusion of H2 bubbles, thereby ensuring the mass transfer efficiency and gas diffusion rate in the HER process under high current, and at the same time, the high specific surface area thereof provides more catalytic active sites, thereby improving the catalytic activity of the HER process. The nickel-molybdenum alloy contained in the electroplated alloy catalyst layer has a high HER catalytic activity, which can further reduce the energy barrier of the hydrogen evolution reaction kinetics, thereby reducing the overpotential of the hydrogen evolution reaction.
[0137] The scanning electron microscopy of the nanoporous alloy catalyst layer prepared by the method for preparing the nanoporous composite electrocatalytic material provided in this embodiment is as follows: Figure 1 The scanning electron microscope image of the prepared nanoporous composite electrocatalyst material with an electroplated alloy catalyst layer is shown in Figure 2 shown by Figure 1 It can be seen that the nanoporous composite electrocatalytic material provided in this embodiment has a nanoporous structure morphology, the nanoporous structure presents a dual interconnected morphology, and the pore diameter of the surface nanoporous structure is about 500nm, and the ligament diameter is about 500nm; Figure 2 It can be seen that the nanoporous composite electrocatalytic material still has a porous nanostructure morphology, and a relatively evenly distributed electroplated catalytic layer is observed on the surface.
[0138] The energy spectrum analysis diagram of the nanoporous composite electrocatalyst material prepared by the preparation method of the nanoporous composite electrocatalyst material provided in this embodiment is as follows: Figure 3a-3d shown by Figure 3a-3d It can be seen that the element composition of the nanoporous composite electrocatalytic material provided in this embodiment is nickel, oxygen, molybdenum, and zinc. Figure 3a-3d The nanoporous composite electrocatalytic materials and the energy spectrum analysis diagrams of nickel, oxygen, molybdenum and zinc therein are respectively Figure 3a-3d It can be seen that nickel, oxygen, molybdenum and zinc are uniformly distributed in the nanoporous composite electrocatalyst material provided in this embodiment, wherein the oxygen element is formed in the nanoporous composite electrocatalyst material during the preparation process of the nanoporous composite electrocatalyst material.
[0139] Example 2
[0140] The preparation method of the nanoporous composite electrocatalytic material described in Example 2 is different from the preparation method provided in Example 1 only in the preparation of the electroplated alloy catalyst layer, the electroplating current density and the electroplating time. In this embodiment, the electroplating current density is 200 mA cm -2 , the electroplating time is 3 min, and the other steps are the same to obtain the nanoporous composite electrocatalytic material of this embodiment.
[0141] The scanning electron microscope image of the nanoporous composite electrocatalyst material prepared by the method for preparing the nanoporous composite electrocatalyst material provided in this embodiment is as follows: Figure 3a and Figure 3b shown by Figure 3a and Figure 3b It can be seen that: the nanoporous composite electrocatalytic material provided in this embodiment still has a nanoporous structural morphology, and a relatively evenly distributed electroplated catalytic layer is observed on the surface.
[0142] The nanoporous composite electrocatalyst material obtained in Example 1-Example 2 was tested, wherein the test temperature was room temperature, the test system was a standard three-electrode system, the counter electrode was a carbon rod, the reference electrode was a Hg / HgO electrode, and the electroplating solution was an oxygen-saturated 1.0M KOH solution. The electrocatalytic analysis of the nanoporous composite electrocatalyst material was performed, and the cathode oxygen evolution performance of the alkaline water electrolysis nanoporous composite electrocatalyst material was shown in the figure below: Figure 4 As shown; the horizontal axis is the overpotential (unit: V), and the vertical axis is the reference current density (unit: mA cm -2 );Depend on Figure 4 It can be seen that the cathode catalyst of the nanoporous composite electrocatalytic material provided in Examples 1 and 2 only needs an overpotential of 255 mV and 334 mV respectively to provide 300 mA cm -2 The base current density.
[0143] The long-term stability performance of the alkaline water electrolysis cathode hydrogen evolution catalysis of the nanoporous composite electrocatalyst material obtained in Example 2 is shown in the figure Figure 5 As shown; wherein, the ordinate is the overpotential (unit: V), and the abscissa is the catalytic time (unit: h); Figure 5 It can be seen that: 300mA cm -2 Under the benchmark current density test conditions, the nanoporous composite electrocatalyst material has excellent stability within 40 hours.
[0144] For the nanoporous composite electrocatalytic materials obtained in Example 1-Example 2, the metal Zn was removed by vacuum vapor dealloying to form a nanoporous alloy catalytic layer; the nanoporous alloy catalytic layer was placed in a Ni, Mo electroplating solution using a hanger to form an electroplated alloy catalytic layer on its surface.
[0145] Therefore, the nanoporous composite electrocatalytic material obtained in Example 1-Example 2 of the present invention obtains a nanoporous Ni alloy structure with a suitable pore size and uniform distribution by setting experimental conditions. This nanoporous structure formed in the alloy layer on the surface can have a firm mechanical contact with the metal substrate of the conductive substrate, effectively preventing the active material from falling off, and the strong bond between the electroplated alloy catalyst layer and the nanoporous structure also increases the bonding strength and structural stability; at the same time, the nanoporous structure can accelerate the penetration of the electrolyte and the diffusion of H2 bubbles, ensuring the mass transfer efficiency and gas diffusion rate in the HER process under high current, and at the same time, its large specific surface area can provide more active sites for the electrocatalytic hydrogen evolution reaction; the nickel-molybdenum alloy contained in the electroplated alloy catalyst layer has a high HER catalytic activity, which can further reduce the energy barrier of the hydrogen evolution reaction kinetics, thereby reducing the overpotential of the hydrogen evolution reaction. Therefore, compared with traditional cathode catalyst materials, the cathode catalyst of the nanoporous composite electrocatalytic material of the present invention can effectively reduce energy consumption and improve energy utilization efficiency when producing hydrogen under industrial high current density, and can realize large-scale industrial application.
[0146] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.
Claims
1. A nanoporous composite electrocatalytic material, characterized in that: It includes a nanoporous alloy catalytic layer and an electroplated alloy catalytic layer formed layer by layer. The nanoporous alloy catalytic layer includes a metal substrate and a nanoporous structure. The nanoporous structure is formed on the surface of the metal substrate. The electroplated alloy catalytic layer is formed on the surface of the nanoporous structure by electroplating.
2. The nanoporous composite electrocatalytic material according to claim 1, characterized in that: The nanoporous structure is formed by alloying an alloy layer formed on the surface of the metal substrate and then subjecting it to a dealloying process.
3. The nanoporous composite electrocatalytic material according to claim 2, characterized in that: The metal substrate includes a first metal or a first metal alloy, and the alloy layer includes the first metal and a second metal or a second metal alloy.
4. The nanoporous composite electrocatalytic material according to claim 3, characterized in that: The first metal includes at least one of nickel, cobalt, copper, and iron, and the second metal includes at least one of zinc, aluminum, manganese, magnesium, and molybdenum.
5. The nanoporous composite electrocatalytic material according to claim 2, characterized in that: The dealloying process includes a gas phase dealloying method or a liquid phase chemical dealloying method.
6. The nanoporous composite electrocatalytic material according to claim 1, characterized in that: The thickness of the nanoporous alloy catalytic layer is 3 μm to 40 μm; the average pore diameter of the pores in the nanoporous structure is 3 nm to 650 nm; the size range of the ligaments in the nanoporous metal substrate is 100 nm to 2.5 μm.
7. The nanoporous composite electrocatalytic material according to claim 1, characterized in that: The electroplated alloy catalytic layer includes an alloy composed of two or more different metal elements.
8. The nanoporous composite electrocatalytic material according to claim 7, characterized in that: The alloy composed of two or more different metal elements includes at least two of nickel, cobalt, molybdenum, iron, tungsten, copper, zinc, aluminum and tantalum.
9. Use of a nanoporous composite electrocatalytic material according to any one of claims 1 to 8, characterized in that: The nanoporous composite electrocatalytic material is used as a cathode catalyst for hydrogen production by alkaline water electrolysis.
10. A method for preparing a nanoporous composite electrocatalytic material, characterized in that: It includes the following steps: S1, covering the surface of a metal substrate with a mixture of metal powder and filler, and forming an alloy layer on the surface of the metal substrate by alloying treatment; S2. The alloy layer is treated by a dealloying process to form a nanoporous structure on the surface of the metal substrate, and the metal substrate and the nanoporous structure on its surface form a nanoporous alloy catalytic layer; S3, placing the formed nanoporous alloy catalyst layer in an electroplating solution, and forming an electroplated alloy catalyst layer on the surface of the nanoporous structure by electroplating.
11. The method for preparing the nanoporous composite electrocatalytic material according to claim 10, characterized in that: The metal powder includes at least one of zinc powder, aluminum powder, manganese powder, magnesium powder, and molybdenum powder; and the filler is alumina or quartz sand.
12. The method for preparing the nanoporous composite electrocatalytic material according to claim 10, characterized in that: Step S1 includes the following steps: S11, mixing the metal powder and the filler to form the mixture; S12, placing the metal substrate in an alloying device, covering the surface of the metal substrate with the mixture, and introducing a protective gas into the alloying device for 15 minutes to 30 minutes; S13. After introducing protective gas into the alloy layering equipment for 15 minutes to 30 minutes, the metal substrate covered with the mixture is annealed to form the alloy layer on the surface of the metal substrate; wherein the annealing temperature is 300°C to 1000°C, and the annealing time is 0.1h to 5h.
13. The method for preparing the nanoporous composite electrocatalytic material according to claim 10, characterized in that: In step S2, the dealloying process adopts a vapor phase dealloying method, which includes: The metal substrate with the alloy layer formed on the surface is placed in a heat treatment furnace for heating, and the alloy layer is decomposed by heating to form the nanoporous structure; wherein the pressure range of the heat treatment furnace is 10 -3 Pa~10 5 Pa, heating temperature is 450℃~850℃, and heating time is 0.5h~3.5h.
14. The method for preparing the nanoporous composite electrocatalytic material according to claim 10, characterized in that: In step S2, the dealloying process adopts a liquid phase chemical dealloying method, and the liquid phase chemical dealloying method includes: placing the metal substrate with the alloy layer formed on the surface thereof into a chemical etching solution, and at a certain etching temperature and etching time, the alloy layer is dealloyed by chemical etching to form the nanoporous structure; The chemical etching solution includes at least one of potassium hydroxide solution, sodium hydroxide solution, sodium carbonate solution, potassium carbonate solution, sodium bicarbonate solution, potassium bicarbonate solution, sodium phosphate solution, sodium monohydrogen phosphate solution, sodium dihydrogen phosphate solution, potassium phosphate solution, potassium monohydrogen phosphate solution, potassium dihydrogen phosphate solution, hydrochloric acid solution, sulfuric acid solution, nitric acid solution, phosphoric acid solution, ammonium chloride solution, ammonium sulfate solution, ammonium nitrate solution, ammonium carbonate solution, ammonium bicarbonate solution, ammonium phosphate solution, ammonium monohydrogen phosphate solution, and ammonium dihydrogen phosphate solution. The concentration of the chemical etching solution is 0.1M to 6M, the etching time is 0.1h to 12h, and the etching temperature is 10°C to 80°C.
15. The method for preparing the nanoporous composite electrocatalytic material according to claim 10, characterized in that: In step S3, the cleaned nanoporous alloy catalyst layer is placed in a chemical plating solution for electroplating using a hanger; The concentration of all solutes in the electroplating solution is 0.01M to 2M, and the electroplating time is between 1min and 60min. The electroplating method is three-electrode constant voltage electroplating or two-electrode constant current electroplating. When the electroplating method is three-electrode constant voltage electroplating, the reference electrode is an Ag / AgCl electrode, the counter electrode is a carbon rod, and the deposition potential is -1V to -2V. When the electroplating method is two-electrode constant current electroplating, the electroplating current density is 5mA cm -2 ~1000mA cm -2 The plating solution temperature is 10°C to 60°C; the electroplating anode is a metal plate having an area larger than that of the nanoporous alloy catalyst layer; and the hanger is a copper hanger or a titanium hanger.
16. The method for preparing the nanoporous composite electrocatalytic material according to claim 10, characterized in that: In step S3, the electroplated alloy catalyst layer includes at least two metal elements selected from nickel, cobalt, molybdenum, iron, tungsten, copper, zinc, aluminum, and tantalum.
17. The method for preparing the nanoporous composite electrocatalytic material according to claim 16, characterized in that: In step S3, if the electroplated alloy catalyst layer includes metallic nickel, the electroplating solution includes a nickel salt, and the nickel salt includes at least one of nickel chloride, nickel sulfate, nickel nitrite, nickel nitrate, nickel hydroxide, nickel acetate, nickel sulfamate, and nickel bromide; If the electroplating alloy catalyst layer includes metallic cobalt, the electroplating solution includes a cobalt salt, and the cobalt salt includes at least one of cobalt chloride, cobalt oxalate, cobalt carbonate, cobalt sulfate, cobalt nitrate, and cobalt acetate. If the electroplating alloy catalyst layer includes metallic molybdenum, the electroplating solution includes a molybdenum salt, and the molybdenum salt includes at least one of sodium molybdate, ammonium molybdate, ammonium dimolybdate, ammonium tetramolybdate, potassium molybdate, magnesium molybdate, and zinc molybdate; If the electroplating alloy catalyst layer includes metallic iron, the electroplating solution includes ferrous salt, and the ferrous salt includes at least one of ferrous chloride, ferrous sulfate, ferrous nitrate, and ferrous bromide.
18. The method for preparing the nanoporous composite electrocatalytic material according to claim 10, characterized in that: In step S3, the electroplating solution further contains additives, and the additives include at least one of sodium citrate, sodium tartrate, sodium chloride, potassium chloride, sodium nitrate, sodium sulfate, potassium sulfate, and potassium nitrate.
19. The method for preparing the nanoporous composite electrocatalytic material according to claim 10, characterized in that: In step S3, the electroplating solution further includes a pH adjuster, and the pH adjuster includes at least one of potassium hydroxide solution, hydrochloric acid solution, sodium hydroxide solution, sulfuric acid solution, ammonia solution, sodium carbonate, and sodium bicarbonate.
20. The method for preparing the nanoporous composite electrocatalytic material according to claim 19, characterized in that: The pH value of the electroplating solution is 7-11.
Citation Information
Patent Citations
Alkaline water electrolysis Ni-based three-dimensional network gradient alloy hydrogen evolution cathode
CN102719846A
Method of producing an electrocatalyst
CN111108233A
Preparation method of trace Cu-doped porous NiFe oxygen evolution electrocatalyst
CN115094469A
Preparation method of nickel-molybdenum-zinc alloy self-supporting cathode material and application of nickel-molybdenum-zinc alloy self-supporting cathode material in alkaline water electrolysis
CN118621352A
Nanoporous composite material with Schottky heterojunction as well as preparation method and application of nanoporous composite material
CN118773665A
Cited By
Porous nickel-molybdenum alloy catalytic electrode for hydrogen production through water electrolysis and manufacturing method of porous nickel-molybdenum alloy catalytic electrode
CN122279646A